High Resolution Sea Ice Drift Estimation using Combined TerraSAR-X and RADARSAT-2 Data: First Tests - Frost, Anja; Jacobsen, Sven; Singha, Suman (2017 IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2017)
High resolution sea ice drift fields, the location and extend of converging and diverging zones as well as ice ridges are most important parameters for ship navigation in ice infested waters. In this paper, we present the prototype of a new processor which is aimed to derive the surface ice parameters on the basis of pairs of space-borne Synthetic Aperture Radar (SAR) data of the same and of different sensors, i.e. from data of different bands, resolutions, and orbits. The study is carried out on image data collected during a joint campaign with the Office of Naval Research (ONR) in the western Arctic in 2015. The algorithm proposed is foreseen to be integrated into near-real time (NRT) processing chain at DLR ground stations in order to provide time-critical information as soon as possible to users and stakeholders.